THE INFLUENCE OF INTELLECTUAL CAPITAL AND CORPORATE SOCIAL RESPONSIBILITY TO THE FINANCIAL PERFORMANCE OF PROFERTY AND REAL ESTATE COMPANIES IN INDONESIA - Endah Dwi Rahayu; Khoirunnisa Azzahra (Universitas Putera Batam, 2021)
In Indonesia there are more and more companies engaged in the property and real estate sector, this indicates a growing economy. This reseach purposes to analyze the effect of intellectual capital and non-performing financing on financial performance. The research was conducted on the property and real estate sub-sector companies listed on the Indonesia Stock Exchange in 2015-2019. By using a purposive sampling technique. The population used in this study is the property and real estate sub-sector listed on the Indonesia Stock Exchange in 2015-2019. The sample of this research is 65 data from 13 companies using purpose sampling technique. The data collected in this research is quantitative data. The data analysis method used is descriptive statistical test, classical assumption test, multiple regression analysis test, determination coefficient test (R2) and hypothesis test with the help of statistical product and service solution (SPSS) software version 24. Based on the results of the t and F test of this study shows that intellectual capital and corporate social responsibility have an effect on the company's financial performance. This research can be used as a benchmark for companies to improve their financial performance through the components of Intellectual Capital (IC) and Corporate Social Responsibility